How does aerodynamics influence physiological responses in middle-distance running drafting? - Beaumont, F.; Bogard, F.; Murer, S.; Polidori, G.; Madaci, F.; Taiar, R. (Mathematical Modelling of Engineering Problems, 2019)
This main goal of this study is to investigate the link between both aerodynamics and physiological responses of an international level middle-distance runner, when running either alone or in drafting position behind two pace makers. A simulation model based on Computational Fluid Dynamics (CFD) methods are used to analyze aerodynamic effects while physiological parameters are experimentally recorded using a lightweight ambulatory respiratory gas exchange system (Cosmed K5©). Experiments were performed at submaximal effort during a 1000 m on-track running test, and simulations were carried out under similar conditions in terms of speed and runners spacing. The results indicate that compared to the baseline (running alone), the drafting position shows a significant aerodynamic reduction in drag area (-33%), which should be responsible for the measured decrease in the following physiological parameters: oxygen consumption (-6%), heart rate (-1%) and energy cost (-33%). The findings of this study suggest running behind two pace makers meaningfully influences the runner's physiology by minimizing air resistance.